Community Needs Assessments in Collaboration with Public Health - Bonilla, Emily (My University, 2017)
This report will detail a field experience completed at the Riley County - K-State Research and Extension office under the supervision of Family and Consumer Sciences Agent Virginia Barnard, MPH. The scope of work includes time spent as the City of Manhattan Wellness Intern and as the Riley County K-State Research and Extension Nutrition Assistant. As a Wellness Intern, the focus was on worksite wellness, environment and policy, and access to healthy foods through vending. As a Nutrition Assistant, the focus was on community nutrition education targeting low socioeconomic status populations and under-served audiences.
Keywords: Community Needs Assessment